(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aims to investigate how consumer decision-making processes are impacted by social media marketing tactics and platforms. The study’s goals were attained using a mixed-methods approach that combined qualitative and quantitative research techniques. The research methodology included a thorough examination of the body of knowledge on consumer behaviour and social media marketing, the creation of a survey questionnaire, the collection of data from a sample of consumers who represented the target market, the evaluation of both quantitative and qualitative data, and the integration of findings to provide advice for companies. Descriptive analysis, ANOVA, multiple regressions, and univariate ANOVA analysis are examples of statistical techniques.According to the study’s results, businesses frequently use Twitter, LinkedIn, Instagram, and Facebook as social media marketing channels to engage with consumers. The results of the study show that effective social media marketing techniques can positively affect consumers’ purchasing decisions. The study’s business recommendations on effective social media marketing strategies that can attract and retain customers are given at the conclusion. The current study advances our understanding of how social media marketing affects consumer decision-making by shedding light on the intricate connections between social media marketing, social media platforms, and consumer behaviour.